An analysis of performance by co-simulation of a wind PMSG using Z-source inverter and coded wireless power control for smart grid applications. (30th March 2019) - Hernandez, Michael; Capovilla, Carlos E.; Casella, Ivan R.S.; Filho, Alfeu J. Sguarezi
Abstract: Wireless signals dispatched from a remote operation center in a smart grid scenario for commanding aerogenerators are susceptible to transmission errors. In this applied context, this paper proposes the use of co-simulation (power and telecommunications) for a full analysis of the performance of a wind permanent magnet synchronous generator using coded wireless power control. To a complete proposal evaluation, the wireless system and the aerogenerator control models are performed to observe the operational conditions of the complete system. The obtained results endorse the operational effectiveness of the aerogenerator with coded wireless power control if an adequate coding technique is applied.